Автоматизация дискретного производства - Бонев Б. Е. Боян Енчев; Бохачев Г. Й. Георги Йосифов; Бояджиев И. К. Илия Кирилов; Волчкевич Л. И.; Семенов Е. И. (Москва, Машиностроение, 1987)
Авт. указаны на обороте тит. л.